The Effect of Regional Competition and Company-sponsored Training on the Productivity-Wage Wedge - Tina Hinz; Jens Mohrenweiser (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
The new training literature argues that imperfect labour market competition drives a wedge between productivity and wage increases in skills. We apply recent advancements in the estimation of production and wage functions to show a compressed wage structure in Germany. We also use regional and industry variation in labour market competitiveness and show that there is a premium on productivity and wages,but the productivity-wage wedge does not diminish in labour markets that are more competitive.
Keywords: J24; M53; R23; 330